Musical scales optimize pitch spacing: a global analysis of traditional vocal music - Steven Brown; Elizabeth Phillips; Khalil Husein; John McBride (Humanities & Social Sciences Communications)
Abstract The dominant model of musical scales in academic theories is derived from instrument tunings. However, the study of vocal scales – most especially in indigenous cultures – has been all but ignored. The voice is almost certainly the original musical instrument, and so an analysis of vocal scales provides a more naturalistic means of understanding the evolution of music. In particular, we explore the idea that the structure of musical scales is a reflection of the vocal imprecision inherent in the way that people sing, regardless of culture. To investigate this issue globally, we carried out a large-scale computational analysis of 418 ethnographic field recordings of vocal songs from indigenous/traditional cultures, spanning the 10 principal musical-style regions of the world, analyzing the number of pitch-classes, the number of interval-classes, the pitch-class distribution, the scale intervals, and scale typology. The results revealed that vocal scales have reliably larger intervallic spacings between pitch-classes than do theory-based and instrumental scales in Western culture. In addition, the mean interval-size of the scales was significantly correlated with people’s imprecision in singing pitches across the world regions. These results lend support to a physiological model in which musical scales optimize pitch spacing in order to accommodate the imprecision inherent in vocal production and thereby maintain distinguishability between pitch-classes during musical communication.